Relation of Religious, Politics, and State in Indonesia: A Comparative Study Soekarno and Abdurrahman Wahid - Mu'iz, Dzikrul Hakim Tafuzi; Nasrulloh, Nasrulloh; Marwinata, Pepy; Mahsunah, Mursyidatul (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2024)
This study aims to compare Soekarno's and Abdurrahman Wahid's (Gus Dur) thoughts regarding the form of state that is relevant in Indonesia. This concerns the relationship between religion, politics, and the state in the context of Indonesia, which is still a polemic that has not found a meeting point in various discussions, so the issue has always been a current discourse because it always experiences fluctuating discourse in the political arena in Indonesia. Soekarno and Abdurrahman Wahid (Gus Dur) are two figures who have significantly contributed to the Indonesian nation; apart from the fact that they have served as presidents, their ideas also quite color the dynamics of thinking about how to state in Indonesia. This paper examines Soekarno and Gus Dur's views on the relationship between religion and the state and then compares the two. This type of research is normative research using a conceptual approach to obtain a comprehensive framework of Soekarno and Gus Dur's thoughts. The conclusion of this research found three forms of relationship between religion and the state, namely integralistic, secularistic, and symbiotic. Soekarno, with his nationalism, emphasized the separation between religion and the state so that it tended to be a secularistic relationship. Meanwhile, Gus Dur, with his contextualist paradigm, prefers to implement Islam as a social ethic, necessitating a symbiotic relationship or mutual benefit and mutual need between religion and the state. [Studi ini bertujuan mengkomparasikan pemikiran Soekarno dan Abdurrahman Wahid (Gus Dur) terkait bentuk negara yang relevan di Indonesia. Hal tersebut mencakup relasi antara agama, politik, dan negara dalam konteks Indonesia yang masih menjadi suatu polemik yang belum menemukan titik temu dalam berbagai perbincangan sehingga topik tersebut selalu menjadi diskursus aktual karena senantiasa mengalami fluctuative discourse dalam percaturan politik di Indonesia. Soekarno dan Abdurrahman Wahid (Gus Dur) merupakan dua tokoh yang berjasa besar bagi bangsa Indonesia selain karena mereka pernah menjabat sebagai presiden, gagasan-gagasan mereka juga cukup mewarnai dinamika pemikiran cara bernegara di Indonesia. Tulisan ini mengkaji pandangan Soekarno dan Gus Dur tentang relasi antara agama dan negara kemudian mengkomparasikan keduanya. Jenis penelitian ini merupakan penelitian normatif dengan menggunakan conceptual approach untuk mendapatkan kerangka pemikiran Soekarno dan Gus Dur secara komprehensif. Kesimpulan penelitian ini menemukan tiga bentuk hubungan antara agama dan negara, yaitu: integralistik, sekularistik, dan simbiotik. Soekarno dengan nasionalismenya lebih menekankan pemisahan antara agama dan negara sehingga lebih cenderung pada hubungan sekuralistik. Sedangkan Gus Dur dengan paradigma kontekstualisnya lebih memilih untuk mengimplementasikan Islam sebagai etika sosial, meniscayakan adanya hubungan simbiotik atau saling menguntungkan, dan saling membutuhkan antara agama dan negara].